Methotrexate-Associated Lymphoproliferative Disorder in a Patient with Psoriasis: A Case Report and Review of the Literature - Afonso, Carolina; Roque, Adriana; Almeida, Cátia; Pimentão, Maria Beatriz; Julião, Maria José; Silva, Rodolfo; Geraldes, Catarina; Gomes, Marília (Case Reports in Hematology, 2022)
Iatrogenic immunodeficiency-associated lymphoproliferative disorders (LPDs) are heterogeneous clinicopathological entities developing in patients receiving immunosuppression. Outside the posttransplant setting, methotrexate (MTX), a drug commonly used for the treatment of autoimmune diseases, is an immunosuppressive agent frequently reported to be associated with LPD. MTX-associated LPD (MTX-LPD) includes a spectrum of lymphocytic proliferations, ranging from polyclonal hyperplasia to malignant lymphoma. MTX-LPD diagnosis can be challenging, as signs and symptoms are often nonspecific and may overlap with those of several other conditions, including exacerbation of the underlying autoimmune disease. Spontaneous regression of LPD after MTX discontinuation is characteristic of MTX-LPD, therefore avoiding chemotherapeutic intervention in a significant proportion of patients. Other cases, however, should receive chemotherapy.